Association Between a TLR2 Gene Polymorphism (rs3804099) and Proteinuria in Kidney Transplantation Recipients - Fei, Shuang; Gui, Zeping; Feng, Dengyuan; Wang, Zijie; Zheng, Ming; Chen, Hao; Sun, Li; Tao, Jun; Han, Zhijian; Ju, Xiaobing; Gu, Min; Tan, Ruoyun; et al. (Frontiers in Genetics, 2022)
Background: The occurrence of proteinuria is one of the evaluation indicators of transplanted kidney damage, and becomes an independent risk factor for poor prognosis after kidney transplantation. Our research sought to understand these potential associations and detect the underlying impact of Single Nucleotide Polymorphisms (SNPs) on proteinuria in kidney transplant recipients. Material and Methods: There were 200 recipients enrolled in this study, from which blood samples were extracted for SNP mutation-related genes detection. RNA sequencing was performed in kidney tissues after kidney transplantation, and the significantly differentially expressed genes (DEGs) were analyzed between the control group and the proteinuria group. Then, the intersection of the genes with SNP mutations and DEGs was conducted to obtain the target genes. Multiple genetic models were used to investigate the relationship between SNPs and proteinuria. In addition, The effect of SNP mutation in the target gene was further validated in human renal podocyte. Results: According to the sequencing results, 26 significant SNP mutated genes and 532 DEGs were found associated with proteinuria after kidney transplantation. The intersection of SNP mutated genes and DEGs showed that toll-like receptor 2 (TLR2) gene was significantly increased in the transplanted renal tissues of patients with proteinuria after kidney transplantation, which was consistent with the results of immunohistochemical staining. Further inheritance model results confirmed that mutations at rs3804099 of TLR2 gene had significant influence on the occurrence of proteinuria after kidney transplantation. In the in vitro validation, we found that after the mutation of rs3804099 on TLR2 gene, the protein expressions of Podocalyxin and Nephrin in podocytes were significantly decreased, while the protein expressions of Desmin and apoptosis markers were significantly increased. The results of flow cytometry also showed that the mutation of rs3804099 on TLR2 gene significantly increased the apoptotic rate of podocytes. Conclusions: Our study suggested that the mutation of rs3804099 on TLR2 gene was significantly related to the generation of proteinuria after kidney transplantation. Our data provide insights into the prediction of proteinuria and may implay potential individualized therapy for patients after kidney transplantation.